Pengembangan LKPD Berbasis Flip PDF Professional pada Pembelajaran Tematik di Kelas V SDN 24 Pontianak Tenggara - Selvia, Selvia; Salimi, Asmayani; Pranata, Rio (FONDATIA, 2023)
The overall objective of this research is to find out the most common way of developing Flip Pdf Professional based LKPD for thematic learning theme 6 sub-theme 2 learning 1 in class V SD Negeri 24 Pontianak Tenggara. Research and Development (R&D) is a research method used by adopting the ADDIE model which does not reach the evaluation stage. The research steps are problem analysis, design, product development, and limited implementation. The research instrument used material and media expert validation sheets as well as student response questionnaires. The results of the study show that at the analysis stage two main things are carried out related to students and the abilities used to develop LKPD. The planning carried out includes selecting the existence of a media plan, planning that underlies the media and planning for the arrangement of research instruments. The development carried out is assembling product items using the Flip Pdf Professional application based on ideas from the validator. The results showed that the achievement of the LKPD surveyed by material experts was in the very proper category (0.89) and the assessment by media experts was in the very feasible class (0.85). After product validation was carried out, a limited implementation was carried out in the form of product trials on 25 VA class students at SDN 24 Pontianak Tenggara. The results of the small and large group trial students' responses to the development of LKPD obtained very good criteria with the average percentage value obtained being the same high (86.73%).